DNA damage assessment in the lymphocytes of construction painters by comet assay. (November 2016) - Kianmehr, Mojtaba; Amiri, Mostafa; Ebrahimzadeh-bideskan, Alireza; Hajavi, Jafar
Background: Exposure to chemicals is inevitable for certain occupational groups, particularly in industrial countries. Some cytogenetic tests such as comet assay are effectively utilized to screen genotoxic effects of these chemicals in humans. The purpose of this study has been to assess the DNA damage in construction painters' lymphocytes using the comet assay. Methods: Fourteen male construction painters with 1 year of required work experience were randomly selected from the list of Painter Union in Gonabad city, Iran. In addition, 14 healthy male non-painters were randomly selected as controls. The DNA damage degree was determined using a fluorescence microscope and CometScore software. The obtained data were analyzed employing independent t -test using SPSS software v. 14 at the significant level of p < 0.05. Results: All participants were non-smokers and non-alcoholics. No significant differences were found between the two groups in terms of age, weight, height, body mass index, and systolic and diastolic blood pressure. The DNA damage in the painter group was significantly greater than that of the control group. Tail length (µm) was 12.63 ± 6.54 versus 2.90 ± 0.84, tail DNA (%) was 4.33 ± 1.84 versus 1.29 ± 0.43, and tail moment (µm) was 1.85 ± 0.98 versus 0.14 ± 0.20 in painter and control groups ( p < 0.001), respectively. Conclusion: The chemicals used in oil paint may increase the DNA damage in painter blood lymphocytes.